Production of Curcumin- Dry- Salted Spot-Fin Spiny Eel (Macrognathus Siamenis) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Macrognathus siamensis is a tropical fish founding in the rivers of Southeast Asia. Coming from the natural resource, it flesh has valuable nutrients. Objective of this research focused on the processing of spot fin spiny eel into the curcumin-dry-salted product by salting and drying method. Different technical experiments were investigated such as the effect of salt, curcumin ratio during soaking, temperature of drying, and packaging storage to chemical, microbial and sensory characteristics of the finished product. Results revealed that dry salting was better than wet salting. With addition of 0.75% of curcumin, drying at 50oC in 4 hours, the curcumin-dry-salted spotfin spiny eel products had the good physicochemical, microbiological and sensory characteristics. By preserving under vacuum at 4oC, the curcumin-dry-salted spotfin spiny eel could be maintained shelf-life for 12 months without any deterioration.Keywords: Spot-fin spiny eel, Macrognathus siamenis, Curcumin, Salting, Drying, Vacuum, Shelf-life.